CONCEPTION OF BULLYING AT COMPREHENSIVE SCHOOL: DISCOURSE ON REASONS, FORMS AND CONSEQUENCES - Targamadzė, Vilija; Valeckienė, Džiuginta (Acta Paedagogica Vilnensia, 2007)
The article attempts to analyze the interpretation spread of conception of bullying in comprehensive school, emphasizing both multi-dimension of bullying and its purposeful linking to bullying forms, reasons and consequences. Researches of Olweus (1999), Smith, (2000) demonstrate that it is topical when analyzing the phenomenon of bullying at comprehensive school. Before the end of sixties and beginning of seventies in the 20th century any manifestation of aggressive behaviour at school used to be treated as violent behaviour and interpreted by different theories of aggression. It is to be noted that agression could be named under general phenomenon, involving both bullying and violent behaviour, though it is evident that entire aggressive behaviour can not be treated as bullying. Stimulus to start analysis of bullying as a phenomenon was given by „Agression in the schools: Bullies and „whipping boys“, the book of Olweus (1978, Swedish version in 1973). Nowadays sound researches of the phenomenon and implementation of interventional strategies are executed in Canada, USA, Australia, New Zealand and other countries (Smith et al, 1999). On international level the notion of „bullying“ is usually employed, as it gives a sense to frightening or hurt of a weaker person, employing strength or power and aiming at making someone to do something (Oxford Advanced Learner’s Dictionary of Current English, 2000). The problem of naming the phenomenon also exists in Lithuania and complexity of it is also justified by the problem of its classification forms. It is to be noted that bullying characterized by different forms, whose spectrum of manifestation is changing rapidly in particular. Bullying leads to long-term consequences both for schoolchildren, who used to be the victims of it, and bullies themselves (Olweus, 1978; Schafer, Korn, Smith, Hunter, Mora-Merchan, Singer, Meulen, 2004). Bullying may have a negative impact on schoolchildren, who appeared to be the victims of it. Monitoring of situation evokes unpleasant sensations and distress, as attention is mostly concentrated on willingness to avoid the status of victim (Zigler, Pepler, 1993). Besides, onlookers of bullying fear to become such victims themselves. Thus, bullying has a negative impact on entire micro-climate at school, since environment becomes soaked with fear and intimidation. Findings • Frequent bullying is a most common form of aggressive behaviour at comprehensive school and is treated as deliberate, frequent negatyve individual or group actions against person, usually weaker and unable to protect himself, aiming at his wounding or injury. Therefore, bullying behaviour is usually characterized by absence of balance on physical and psychological strength between bully and his victim, employment of physical and verbal actions, causing pain to the victim of bullying, deliberate hurt of another person and frequent recurrence of bullying actions. • Direct and indirect forms of bullying are separated out, though scientific sources also distinguish between physical, verbal and relation based forms of bullying. Nowadays this phenomenon takes the shape of modern forms, often linked to IT. Besides, most frequent is bullying, based on personal peculiarities or body shape, racial background, confession. It is also divided into bullying, directed against disability, based on sexual abuse against schoolchildren of comprehensive schools. • It is not yet examined, how natural psychical properties, like impulsiveness, sensibility and emotionality, influence manifestation of aggressiveness among children and what part of it depends upon child’s environmental factors, like upbringing methods of parents, lack of love and warmth, violence that they experience at home. • Bullying is not only the reason of short-term consequences for the victim. It also causes longterm consequences both for the victim and the bully. In the future bullying is likely to turn into other forms of frequent aggressive behaviour. A direct relation between delinquent behaviour and crimes in adult age has been identified. Bullying, experienced in childhood, is likely to be related to behavioural, communicative, emotional problems of adult age.
Keywords: agression; bullying; forms of bullying; initiator of bullying; victim of bullying